Aproximaciones a una psicología de la exclusión (2011)
ABSTRACT: The author outlines the concept of positive otherness or negative around the social and institutional practices of exclusion, as long as the recognition of the other one as different, inside the symbolic sphere of the social thing. It recaptures the thought western stigmatizing and it opposes this the modern thought that exalts the recognition of the diverse thing as inclusion form, that transforms it into a threatening speech for the project European homogenizing. It shows how the task of a psychology of the exclusion, is the analysis of the effacement practices, rejection and non recognition of the other one in the social thing, as well as its consequences in the subjective thing and in the identity, understanding the recognition like the acceptance and inclusion of the differences in the social practices. This as allusion to that outlined by Axel Honnet who locates the love, the right and the solidarity to the base of practical inclusive, in opposition to the forms of contempt as the one “weakening of the personal identity in their entirety”.